Радиационный анизотропный оптикотермоэлемент с боковым термостатированием - Ashcheulov, A. A.; Okhrem, V. G. (PE "Politekhperiodika", Book and Journal Publishers, 2004)
Taking into account the Bouguer–Lambert law, the inhomogeneous heat conduction equation was solved for a circular cylinder made of thermoelectrically anisotropic material. Expressions were obtained for the transverse thermoelectric emf and the main characteristics of a radiation anisotropic optico-thermoelement, which makes it possible to control the radiant energy flux in the region of optical transparency of the material from which it is made. A receiver design is proposed that does not distort the amplitude-phase characteristics of the transmitted radiant flux.